Parameters of the drying medium and dried hops in belt dryer - Adolf Rybka; Petr Heřmánek; Ivo Honzík; Karel Krofta (Research in Agricultural Engineering, 2017)
An important factor in hop growing is the process of drying. For this purpose belt dryers with follow-up conditioning are the most widespread but they are not ideal. In this respect, an analysis of the drying process was carried out in the belt dryer of Agrospol Velká Bystřice Co., Ltd. for the 'Saaz' hop variety. Drying parameters were monitored by means of fixed sensors, continuously sensing data loggers and samples taken for laboratory analysis (hop moisture, alpha and beta bitter acids, Hop Storage Index (HIS). The process of drying showed that hops are practically dry (10 ± 2.0% of moisture) already at the end of the second belt or possibly at the beginning of the third belt. It was also proved that hops are over-dried (moisture of 4 to 8%) and then they are adjusted by conditioning to the final moisture content of 8-10%. Excessive drying leads to cone disintegration, which makes any manipulation with hops for purposes of further processing difficult and results in greater losses of lupulin.